2012
DOI: 10.1002/jssc.201101083
|View full text |Cite
|
Sign up to set email alerts
|

Protein adsorption on DEAE ion‐exchange resins with different ligand densities and pore sizes

Abstract: Ion exchange chromatography (IEC) is a common and powerful technique for the purification of proteins. The ligand density and pore properties of ion-exchange resins have significant effects on the separation behaviors of protein, however, the understandings are quite limited. In the present work, the adsorption isotherms of bovine serum albumin (BSA) and human serum albumin (HSA) were investigated systematically with series of diethylaminoethyl (DEAE) ion-exchange resins, which have different ligand densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…S1. It was found that two properties of the resins, ligand density and pore size, had an integrative impact on the adsorption of bovine IgG, which is similar to our previous work with bovine serum albumin (BSA) [26]. Therefore, the influences of ligand density, pore size, and protein characteristics were investigated in detail as following.…”
Section: Adsorption Isothermssupporting
confidence: 54%
See 4 more Smart Citations
“…S1. It was found that two properties of the resins, ligand density and pore size, had an integrative impact on the adsorption of bovine IgG, which is similar to our previous work with bovine serum albumin (BSA) [26]. Therefore, the influences of ligand density, pore size, and protein characteristics were investigated in detail as following.…”
Section: Adsorption Isothermssupporting
confidence: 54%
“…For bovine IgG, a and b are 48.37 and 204.84, respectively. For BSA, the parameters of a and b are 47.08 and 136.52, respectively [26]. It can be found that the slopes of correlation lines are nearly same for two proteins, indicating that the integrated effects of ligand density and pore size on the adsorption capacity of bovine IgG and BSA are similar.…”
Section: Effects Of Ligand Density and Pore Sizementioning
confidence: 86%
See 3 more Smart Citations